2021
DOI: 10.3390/microorganisms9061262
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Properties of Edible Mushrooms and Herbal Teas in Gut Microbiota Modulation

Abstract: Edible mushrooms are functional foods and valuable but less exploited sources of biologically active compounds. Herbal teas are a range of products widely used due to the therapeutic properties that have been demonstrated by traditional medicine and a supplement in conventional therapies. Their interaction with the human microbiota is an aspect that must be researched, the therapeutic properties depending on the interaction with the microbiota and the consequent fermentative activity. Modulation processes resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 118 publications
0
9
0
Order By: Relevance
“…Mushrooms contain bioactive ingredients that can modulate gut microbiota ( Ma et al, 2021 ; Vamanu et al, 2021 ). LPS-induced MIA offspring exhibit a microbiome profile similar to that of humans with ASD ( Lee et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mushrooms contain bioactive ingredients that can modulate gut microbiota ( Ma et al, 2021 ; Vamanu et al, 2021 ). LPS-induced MIA offspring exhibit a microbiome profile similar to that of humans with ASD ( Lee et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Microbial dysbiosis is correlated with behavioral abnormalities and neuropathology ( Vuong and Hsiao, 2017 ). Mushrooms are functional foods containing various biologically active compounds that can mitigate microbial dysbiosis ( Cheung et al, 2020 ; Vamanu et al, 2021 ). Gut microbiota transplantation (primarily with a mixture of bifidobacteria , streptococci, and lactobacilli) is a therapeutic method used to alter microbiome profiles and improve neurobehavioral symptoms ( Kang et al, 2017 ; Fattorusso et al, 2019 ; Chen et al, 2020 ; Abuaish et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the analysis of Arctium lappa L root components, it can be known that Arctium lappa L contains bioactive polysaccharides, polyphenols, and other substances. In fact, studies have found that plant polysaccharides and plant polyphenols have a certain effect on ameliorating glucose and lipid metabolism disorders, especially having anti-diabetic, anti-cancer, and ameliorating effects on obesity (Luo, Mu, & Sun, 2021;Vamanu, Dinu, Pelinescu, & Gatea, 2021). In particular, plant polysaccharides and plant polyphe- It is important that the hepatic lipid metabolism will eventually affect the process of body fat accumulation.…”
Section: Disscus Ionmentioning
confidence: 99%
“…Indeed, kiwifruit has been shown to potentiate sleep via pathways implication serotonin and GABA [41,42]. On a similar theme, another article reviews edible mushrooms as microbiome-modulating functional foods [43]. Mushrooms are rich sources of β-glucan polysaccharides that have a prebiotic effect.…”
mentioning
confidence: 99%